2012
DOI: 10.1038/mt.2011.263
|View full text |Cite
|
Sign up to set email alerts
|

Progress Toward In Vivo Use of siRNAs-II

Abstract: RNA interference (RNAi) has been extensively employed for in vivo research since its use was first demonstrated in mammalian cells 10 years ago. Design rules have improved, and it is now routinely possible to obtain reagents that suppress expression of any gene desired. At the same time, increased understanding of the molecular basis of unwanted side effects has led to the development of chemical modification strategies that mitigate these concerns. Delivery remains the single greatest hurdle to widespread ado… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
190
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 207 publications
(191 citation statements)
references
References 302 publications
1
190
0
Order By: Relevance
“…37 In general, mismatches in the region 3' to the seed sequence of the siRNA promoted robust single-nucleotide discrimination. 38 Nevertheless Ohnishi et al 39 showed that optimal positioning of a singlenucleotide variation depends on the target sequence itself.…”
Section: Discussionmentioning
confidence: 99%
“…37 In general, mismatches in the region 3' to the seed sequence of the siRNA promoted robust single-nucleotide discrimination. 38 Nevertheless Ohnishi et al 39 showed that optimal positioning of a singlenucleotide variation depends on the target sequence itself.…”
Section: Discussionmentioning
confidence: 99%
“…However, its instability in the blood and the low permeability of the plasma membrane requires drug delivery systems that target specific cells in order to achieve an effective therapy by siRNA [6,7]. We previously developed a liposomal siRNA system, a multi functional nano-device (MEND) [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…However, siRNA itself cannot diffuse across the plasma membrane due to its high molecular weight and hydrophilicity, and intravenously administered siRNA is subject to rapid renal clearance and enzymatic degradation by ribonucleases. Therefore, a delivery vehicle or chemical modification is needed to stabilize the siRNA cargo in the bloodstream, deliver siRNA to the target cell in a target organ, circumvent endo/lysosomes degradation and increase cellular uptake [20,21]. A large variety of delivery materials, including polymers [22], liposomes [23][24][25], micelles [26], peptides [27] and proteins [28], are currently under development, in attempts to overcome these obstacles associated with in vivo siRNA delivery.…”
Section: Sirna Delivery To Tumors and The Tumor Vasculature Using A Pmentioning
confidence: 99%